Informe preliminar sobre una tablilla del taller de Isin en una colección particular española - Sanchiz Alvarez de Toledo, Hipólito (Gerión. Revista de Historia Antigua, 2005)
The Isin Craft Archive, attached to the palace of this city, is one of the few economics archives early second millenium that is preserved and could be studied as a whole. One of the more than nine hundred clay tablets scatered by the whole world from this archive was found in a spanish private colecction, being a recieve of raw materials.